Partidos políticos e a institucionalização da política de saúde brasileira: análise das medidas provisórias e decretos da saúde (1989-2018) - Aizza, Leila Eliane (Universidade Federal de São Carlos, 2023)
After the country's redemocratization, the main actors who continued the institutionalization of public policies were political parties. Among the legislative initiation institutes guaranteed to the Executive, provisional measures and decrees are institutional resources exclusive to presidents. At the same time, they are strategies capable of quickly changing the congressional agenda and guaranteeing the implementation of their preferences over other political actors. In this sense, this thesis aims to answer the central question of how the Executive Branch formed by governments of different ideological hues institutionalized health policy? In this sense, the hypothesis that guides the development of this research is that parties on the right of the political spectrum tend to commodify access, through the increase in complementary health to the detriment of public health, as they consider it an expense or expense that compromises the public budget. On the other hand, parties on the left tend to prioritize the expansion of redistributive and universalist policies when allocating public funds. Considering the theoretical contribution of Historical Institutionalism for the development of quantitative and qualitative research and the analysis of government programmatic documents. The main conclusion is that parties on the left of the political spectrum promoted the universalization of the Unified Health System but did not become an obstacle to the expansion of private healthcare in the country.
Political parties and the institutionalization of Brazilian health policy: analysis of provisional measures and decrees (1989-2018)
Keywords: Institucionalização da saúde; SUS; Partidos políticos; Presidencialismo de coalizão; Institutionalization of health; SUS; Political parties; Coalition presidentialism; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS